White Eskimo : Knud Rasmussen's fearless journey into the heart of the Arctic - Bown, Stephen R. (Da Capo Press, a member of the Perseus Books Group, 2015)
"While Amundsen, Franklin, and Peary were first to explore the furthest geographical reaches of the Polar North, Knud Rasmussen was the first to explore its culture and its soul. Part Danish, part Inuit, the famed explorer anthropologist made an epic three year journey by dog sled from Greenland to Alaska recording not only the landscapes but also the songs and stories of the Eskimo people. In the ranks of the great explorer/writers who opened hitherto impenetrable cultures to the West--T.E. Lawrence in the Mideast, Wilfred Thesiger among the Bedouin, Richard Burton in Africa or among the Sufi--Rasmussen stars not only for his physical courage and ability to assimilate into the life of indigenous peoples, but also for the beauty of his writing. Across Arctic America and his collection of Eskimo songs and stories are classics of Polar literature. There has been no full-scale biography of Rasmussen in English, and Stephen Bown's splendidly received life of Roald Amundsen makes him the perfect writer to record the great journeys and fascinating life of the Inuit from Greenland through the Northwest Passage, to Alaska"--